Resistin facilitates VEGF-A-dependent angiogenesis by inhibiting miR-16-5p in human chondrosarcoma cells - Chen, Shiou-Sheng (Cell Death Dis, 2019)
Resistin is an adipokine that is associated with obesity, inflammation, and various cancers. Chondrosarcomas are primary malignant bone tumors that have a poor prognosis. VEGF-A is a critical angiogenic factor that is known to promote angiogenesis and metastasis in chondrosarcoma. It is unknown as to whether resistin affects human chondrosarcoma angiogenesis. In this study, we show how resistin promotes VEGF-A expression and subsequently induces angiogenesis of endothelial progenitor cells (EPCs). Resistin treatment activated the phosphatidylinositol-3-kinase (PI3K) and Akt signaling pathways, while PI3K and Akt inhibitors or siRNA diminished resistin-induced VEGF-A expression. In vitro and in vivo studies revealed the downregulation of micro RNA (miR)-16-5p in resistin-induced VEGF-A expression and EPCs angiogenesis. We also found a positive correlation between resistin and VEGF-A expression, and a negative correlation between resistin and VEGF-A with miR-16-5p in chondrosarcoma patients. These findings reveal that resistin facilitates VEGF-A expression and angiogenesis through the inhibition of miR-16-5p expression via PI3K/Akt signaling cascades. Resistin may be a promising target in chondrosarcoma angiogenesis.